EUROPE'S EXPERIENCE IN DEVELOPING A "GREEN ECONOMY" AND ATTRACTING INVESTMENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the investments and experience of the leading countries of the European region, which consists of a large number of countries of the world, under the "Green Economy" program. These leading countries include Germany, Sweden, Norway, Denmark, Istanbul and France.  and used increased taxes and criminal liability to prevent many people from harming the environment. Collected taxes were reinvested in attracting and improving technologies to create renewable energy sources and reduce environmental damage. This situation continues today is coming.